Functional training improves cognitive function, functional fitness, and BDNF levels in older women with mild cognitive impairment: a randomized controlled trial - Resende-Silva, Salviano; de Resende-Neto, Antônio Gomes; Vasconcelos, Alan Bruno Silva; Pereira-Monteiro, Marcos Raphael; Pantoja-Cardoso, Alan; Santana Santos, Laíza Ellen; Carvalho Lima, Newton Benites; Jesus Santos, José Lucas de; Aragão-Santos, José Carlos; Schimieguel, Dulce Marta; Santos, José Ronaldo dos; Da Silva-Grigoletto, Marzo Edir (Frontiers in Physiology, 2025)
IntroductionTo oppose the aging-related cognitive and functional decline, the efficacy of different training methods has been tested, aiming body multisystemic adaptations. In this sense, Functional Training (FT) has shown relevant results in the physical fitness of older adults. However, little is known about its impact on older women with mild cognitive impairment (MCI).ObjectiveTo compare the effects of functional and aerobic training on cognitive function and functional fitness in older women with mild cognitive impairment.MethodsSixty-eight older women completed a 16-week intervention through three groups: 1) Functional Training (FT: n = 28; mean age = 67.5 ± 4.8 years), 2) Aerobic Training (AT: n = 22; mean age = 66.3 ± 4.6 years), and 3) Control Group (CG: n = 18; mean age = 67.5 ± 4.6 years). The training sessions did occur three times per week, with a duration of 50 min per session for both exercised groups. The training load was quantified daily in the FT group. Cognitive function, serum levels of Brain-Derived Neurotrophic Factor (BDNF), and functional fitness were assessed pre- and post-intervention.ResultsFT and AT groups showed improvements in cognitive status (FT: d = 0.99, p ≤ 0.001; AT: d = 0.97, p ≤ 0.001) and semantic memory (FT: d = 0.95, p < 0.001; AT: d = 0.97, p < 0.001); however, only FT led to improvements in executive function (d = 0.63, p = 0.043) and increased serum BDNF levels (d = 0.95, p = 0.011). Regarding functional fitness, both groups showed improvements in gait and stand up ability, as well as cardiorespiratory fitness. However, only FT improved dexterity and upper limb strength. No statistically significant differences were observed between the FT and AT groups in the measured outcomes.ConclusionBoth FT and AT improve cognitive function and functional fitness in older women with mild cognitive impairment. However, in addition to eliciting a greater magnitude of effects on some outcomes, FT was the only intervention to modulate peripheral BDNF concentration.